2014
DOI: 10.1542/peds.2013-1739
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical and Asymmetrical Growth Restriction in Preterm-Born Children

Abstract: OBJECTIVE: To determine how symmetric (proportionate; SGR) and asymmetric (disproportionate; AGR) growth restriction influence growth and development in preterms from birth to 4 years. METHODS: This community-based cohort study of 810 children comprised 86 SGR, 61 AGR, and 663 non–growth restricted (NGR) preterms, born in 2002 and 2003. Symmetrical growth restriction was defined as a birth weight below the 16th percentile (–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 27 publications
(45 reference statements)
3
53
0
1
Order By: Relevance
“…6, 3133 Such complexity makes it difficult to define clinical growth objectives and suggests that forcing somatic growth with caloric supplementation is an oversimplified approach. Weight gain without a proportional increase in length may be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…6, 3133 Such complexity makes it difficult to define clinical growth objectives and suggests that forcing somatic growth with caloric supplementation is an oversimplified approach. Weight gain without a proportional increase in length may be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of outcomes in preterm infants growth-restricted at birth used z-scores to define restricted growth and classify infants as either symmetric or asymmetric, but did so with measurements obtained at a single time point (birth). 8 Using a single measurement, such as z-score at birth or at discharge, prevents the ability to draw conclusions about the pattern of in-hospital growth. In addition, doing so would lead to exclusion and inclusion bias, whereby some infants with poor growth would be excluded (HC remains greater than a specified z-score or percentile) and others with ‘normal’ postnatal growth might be included (HC remains less than specified z-score or percentile).…”
Section: Discussionmentioning
confidence: 99%
“…Small for gestational age neonates born term and preterm with relative head sparing have neurodevelopmental outcomes that are significantly better than those babies whose head circumference percentiles are the same or lower than their birthweight percentiles. 8, 9, 10 The objective of this study was to compare neurodevelopmental outcomes in postnatal growth-restricted extremely preterm infants with and without PHS.…”
Section: Introductionmentioning
confidence: 99%
“…Bocca-Tjeertes et al, in a study examining how symmetric growth restriction and asymmetric growth restriction influence growth and development in preterms from birth to 4 years, reported that up to age 4 years, symmetric growth restriction and asymmetric growth restriction preterm-born children failed to catch up on weight and height sufficiently, and that these preterm children could not keep up with the growth velocity of their non-growth restriction counter-parts. But, on the other hand, the HC growth of symmetric growth restriction exceeded that of asymmetric growth restriction and non-growth restriction, but still remained lower at age 1 year [58].…”
Section: Discussionmentioning
confidence: 80%